Modelling of distribution system in a factory warehouse using arena (Pemodelan sistem pengedaran gudang kilang menggunakan arena) - Brenda Chong; Sakhinah Abu Bakar; Choong-Yeun Liong (Penerbit Universiti Kebangsaan Malaysia, 2012)
Warehousing represents material storage and physical management processes as well as the methods used by these processes that include all material movement and storage. Distribution system or logistics is a combination of processed functions to manage materials and products from manufacturer to consumer. This research focuses on the study of the warehouse distribution system of a cement factory. The processes involved in this system are modelled using simulation to study the operation in the factory warehouse. Data for building the model were collected through interviews and observation of the whole operation in the warehouse. A computer simulation model is designed, built and run using Arena. Results obtained from the simulation model were analysed to identify the weaknesses of the current system and improvement models were proposed. A total of five improvement simulation models were investigated. The effects of models on customer average waiting times at the various checking points and the model output are analysed. Overall, the best improvement model has succeeded in reducing the average customer waiting time and increased the total customers served in the daily operation of the system very significantly.